Linking pinch analysis and shifted temperature driving force plot for analysis and retrofit of heat exchanger network. (15th September 2021) - Fu, Dianliang; Yu, Zeting; Lai, Yanhua
Abstract: The retrofit of heat exchanger network often needs topology changes to overcome the network pinch to increase heat recovery. It is difficult to maximize energy recovery and minimize topology changes. Owing to good interactive and visualized effects, graphical tools are widely applied in the retrofit. However, for a heat exchanger network with different minimum temperature differences, it becomes difficult to screen retrofit options to avoid crossing the pinch. An efficient graphical tool is needed during retrofit. The shifted temperature driving force plot is proposed to solve this problem by shifting the stream temperature. With the aid of Pinch Analysis, the ideal regions are divided to indicate where heat exchange matches should be located. The emerged stagger of ideal regions before shifting the stream temperature can be avoided. This makes the screening of retrofit strategies easy and convenient. The retrofit of an industrial case is conducted with this graphical tool. The key changes are for the heat exchange matches that cross the pinch. Obtained results show that more energy is recovered with fewer topology changes, thereby yielding improved economic benefits. Application of the shifted temperature driving force plot illustrates its effectiveness in finding better retrofit solutions. Graphical abstract: Image 1 Highlights: Analyzing energy inefficiency of HEN is simple. Avoid the stagger of ideal regions determined by Pinch Analysis. Retrofitting the HEN with multiple MTDs is more convenient. Screening retrofit solutions can rely on the good user interactivity.